Psychosocial Outcomes of Children and Adolescents With Severe Congenital Heart Defect: A Systematic Review and Meta-Analysis. (17th November 2018) - Abda, Assil; Bolduc, Marie-Eve; Tsimicalis, Argerie; Rennick, Janet; Vatcher, Dylan; Brossard-Racine, Marie
Abstract: Objective: Over the past 20 years, there has been a growing interest in the psychosocial outcomes of children and adolescents born with a congenital heart defect (CHD). This systematic review and meta-analysis aims to appraise and synthesize current literature on the psychosocial outcomes of children and adolescents with severe CHD. Methods: A search of studies examining psychosocial outcomes in children and adolescents with severe CHD was performed. Meta-analyses were used to calculate the prevalence of psychosocial impairments and the standardized mean differences between cases and controls. Results that were not included in the meta-analysis were collated using descriptive statistics. Results: A total of 16 studies were included in this review, and results were summarized according to three domains: behavior, social cognition, and self-esteem. Results from a meta-analysis identified that 25% of children and adolescents with CHD presented behavioral problems. Children and adolescents with CHD had more problematic behavior than healthy peers (standardized mean difference; g  = 0.71). Young people with CHD had significantly more difficulties inferring on the mental states of others (standardized mean difference; g  = 0.72). In contrast, identifying the emotions of others and self-esteem was not statistically different from healthy controls. Conclusion: This review and meta-analysis provides evidence to support the presence of psychosocial difficulties in children and adolescents born with a severe CHD giving grounds for the systematic assessment of behavior and social cognition during their clinical follow-up.